Community-acquired Klebsiella spp Meningitis/Invasive Infection in Filipino-descent Patients Living in Greece: A Case Series - Giorgos Marinakis (European Journal of Case Reports in Internal Medicine, 2021)
Klebsiella spp community-acquired meningitis caused by hypervirulent strains is well described as part of a distinct syndrome consisting of liver abscess and multiple septic metastatic lesions (Klebsiella pneumoniae invasive syndrome) occurring usually in diabetic, alcoholic, elderly or cancer patients, in Taiwan and other South-East Asian countries. In Western countries, these infections are very rare in natives and usually occur in patients of Asian origin. We report three cases of Filipino-origin patients, residents of Greece, with community-acquired invasive Klebsiella meningitis, who were treated in our ICU over a 10-year period.